The Role of Gamma Oscillations During Integration of Metaphoric Gestures and Abstract Speech - He, Yifei; Nagels, Arne; Schlesewsky, Matthias; Straube, Benjamin (Frontiers in Psychology, 2018)
Metaphoric co-speech gestures are commonly used during daily communication. They communicate about abstract information by referring to gestures that are clearly concrete (e.g., raising a hand for ‘the level of the football game is high’). To understand metaphoric co-speech gestures, a multisensory integration at semantic level is necessary between abstract speech and concrete gestures. While semantic gesture-speech integration has been extensively investigated using fMRI, evidence from electroencephalography (EEG) is rare. In the current study, we set out an EEG experiment, investigating the processing of metaphoric vs. iconic co-speech gestures in different contexts, to reveal the oscillatory signature of metaphoric gesture integration. German participants (n=20) viewed video clips with an actor performing both types of gestures, accompanied by either comprehensible German or incomprehensible Russian speech, or speaking German sentences without any gestures. Time-frequency analysis of the EEG data showed that, when gestures were accompanied by comprehensible German speech, metaphoric gestures elicited decreased gamma band power (50-70Hz) between 500-700ms in the parietal electrodes when compared to iconic gestures, and the source of this effect was localized to the right middle temporal gyrus. This difference is likely to reflect integration processes, as it was reduced in the Russian language and no-gesture conditions. Our findings provide the first empirical evidence suggesting the functional relationship between gamma band oscillations and higher-level semantic processes in a multisensory setting.